2007
DOI: 10.1007/s12264-007-0006-1
|View full text |Cite
|
Sign up to set email alerts
|

Negative correlation of Nogo-A with the malignancy of oligodendroglial tumor

Abstract: Objective Nogo-A is an axon regeneration inhibitor, and its function in central nervous system (CNS) is still unknown. The present study is to explore the relationship between the expression of Nogo-A and the malignancy of oligodendroglial tumors in patients. Methods Tumor tissue samples with different malignancy grade were obtained from the hospitals. The samples used for detection had been diagnosed as oligodendroglial tumors (oligodendroglioma or anaplastic oligodendroglioma). The expression of Nogo-A was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Furthermore, it was reported previously that Nogo-A expression correlated negatively with the malignancy grade of oligodendrogliomas (73). In this case, a high expression of Nogo-A may restrict vascularization of the oligodendroglioma and thereby limit the tumor growth.…”
Section: Discussionmentioning
confidence: 58%
“…Furthermore, it was reported previously that Nogo-A expression correlated negatively with the malignancy grade of oligodendrogliomas (73). In this case, a high expression of Nogo-A may restrict vascularization of the oligodendroglioma and thereby limit the tumor growth.…”
Section: Discussionmentioning
confidence: 58%
“…18 RTN4 expression has also been negatively correlated with the malignancy grade of oligodendroglial tumors. 19 NFIB is a transcription factor gene that has been associated with MYB-NFIB Ribosomal protein that is a component of the 60S subunit À2.02 Figure 1 Hierarchical cluster analysis using the most significant differentially expressed genes (y axis) revealed that both actinic keratosis (A) vs normal skin (N) and squamous cell carcinoma (S) vs normal skin (x axis) demonstrated distinct genetic signatures. Downregulated genes are in blue and upregulated genes are in red.…”
Section: Discussionmentioning
confidence: 99%
“…32 Interestingly, Nogo-A expression seems to negatively correlate with the malignancy grade of oligodendrogliomas 42 and to serve as a tool to differentiate between oligodendrogliomas and the more densely vascularized glioblastomas, 43 suggesting that Nogo-A may also be involved in regulation of neo-angiogenesis in brain tumors.…”
Section: Nogo-a Deficiency Augments Vessel Density In Developing Cns mentioning
confidence: 99%